Photographic evidence of the Himalayan marmot Marmota himalayana (Hodgson, 1841) from Tsum Valley, Manaslu Conservation Area, Nepal - Poudel, Basu Dev; Shrestha, Sujan; Bhattarai, Rabindra; Rai, Shikhar; Adhikari, Dipendra (Nepalese Journal of Zoology, 2024)
The Himalayan marmot (Marmota himalayana) remains one of Nepal’s lesser-known rodent species. The article discusses first photographic evidence of Himalayan marmot within the alpine grasslands of Tsum Valley, Manaslu Conservation Area, Nepal. Himalayan brown bear (Ursus arctos) pugmarks were also observed close to the marmot's burrow sites. The Himalayan brown bear seems to be one of the potential natural predators of the marmots in the area.